The Application of Milkrun to Reduce Transportation Costs For Automotive After Sales Products During Covid-19 Pandemic: Case study - Taufik, Deni Ahmad; Setiawan, Setiawan; Atikno, Welly (Proceeding Mercu Buana Conference on Industrial Engineering, 2023)
The Covid-19 pandemic has put all businesses in a downturn. This has an impact on the After Sales business such as service parts, accessories and domestic inhouse parts due to the Covid19 pandemic. During the Covid-19 was a very difficult year for the four-wheeled automotive industry in Indonesia where sales decreased drastically from an average of not less than 1 million units to only 600 units a year. This study aims to reduce transportation costs during ongoing business processes. The method used is Milkrun. The research results found that the calculation of transportation costs, it is found that the transportation costs in FY20 are 4,809 MIDR per year because the supplier directly sends the product to the customer so that the transportation cost is based on the distance between the supplier and the customer. By using the milkrun method, transportation costs can be reduced to 3,219 MIDR because the moving transporters take parts from several suppliers that are quite close